Building constructions characteristics and mechanical properties of confined masonry walls in San Miguel (Puno-Peru) - Tarque, Nicola (2022)
House self-construction and self-management are very common in different cities in Peru, which is the case in several areas in the district of San Miguel (Puno). This is due to the lack of financial resources to hire professionals to design and construct their houses. Therefore, many residents build without technical guidance and materials without quality standards. As a result, the buildings in the area have various construction pathologies that demonstrate their high seismic vulnerability, which indicates that the guidelines established in the Peruvian Masonry Design Code NTE 070 are not followed. Therefore, as a first step towards evaluating the seismic vulnerability of the houses in San Miguel, it was decided to evaluate the construction pathologies and typologies by conducting a survey. Subsequently, to characterize and evaluate the physical-mechanical properties of the masonry walls, 24 piles and 24 small walls were built and tested. The materials tested were obtained from the urban area of the same study place. According to the experimental tests, it was observed that the axial compression and diagonal shear values of the prisms are lower than the minimum values specified in the Peruvian Construction Code, and this would increase the seismic vulnerability of the constructions. Therefore, many of the houses in the district could suffer significant damage and even collapse in a seismic event.